2022
DOI: 10.21203/rs.3.rs-1408493/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The tryptophan catabolite or kynurenine pathway in COVID-19 and critical COVID-19: a systematic review and meta-analysis

Abstract: Background: Coronavirus disease 2019 (COVID-19) is accompanied by activated immune-inflammatory pathways and oxidative stress, which both may induce indoleamine-2,3-dioxygenase (IDO), a key enzyme of the tryptophan (TRP) catabolite (TRYCAT) pathway. The aim of the current study was to systematically review and meta-analyze the TRYCAT pathway status including levels of TRP and kynurenine (KYN) and IDO activity, as assessed using the KYN/TRP ratio. Methods: This systematic review was performed in December 2021 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(59 reference statements)
2
3
0
Order By: Relevance
“…The current meta-analysis indicates that there is no overactivation of the TRYCAT pathway in severe forms of affective disorders, which are, nevertheless, accompanied by a mild chronic immune-inflammatory response. Similar findings were recently reported in Alzheimer’s disease, another disorder accompanied by a mild chronic inflammatory process (Almulla, Supasitthumrong et al 2022, Almulla, Thipakorn et al 2022). In contrast, the TRYCAT pathway is more pronounced in conditions characterized by severe acute inflammatory conditions such as COVID-19 infection (Almulla, Supasitthumrong et al 2022) and treatment with IFN-α (Bonaccorso, Marino et al 2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current meta-analysis indicates that there is no overactivation of the TRYCAT pathway in severe forms of affective disorders, which are, nevertheless, accompanied by a mild chronic immune-inflammatory response. Similar findings were recently reported in Alzheimer’s disease, another disorder accompanied by a mild chronic inflammatory process (Almulla, Supasitthumrong et al 2022, Almulla, Thipakorn et al 2022). In contrast, the TRYCAT pathway is more pronounced in conditions characterized by severe acute inflammatory conditions such as COVID-19 infection (Almulla, Supasitthumrong et al 2022) and treatment with IFN-α (Bonaccorso, Marino et al 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were recently reported in Alzheimer’s disease, another disorder accompanied by a mild chronic inflammatory process (Almulla, Supasitthumrong et al 2022, Almulla, Thipakorn et al 2022). In contrast, the TRYCAT pathway is more pronounced in conditions characterized by severe acute inflammatory conditions such as COVID-19 infection (Almulla, Supasitthumrong et al 2022) and treatment with IFN-α (Bonaccorso, Marino et al 2002). In those conditions, cytokine induced TRP depletion (also known as TRP starvation) is a key element in the innate immune response that impedes intruding pathogens and results in anti-inflammatory effects (Maes, Leonard et al 2011, Almulla and Maes 2022).…”
Section: Discussionsupporting
confidence: 90%
“…First, the paper would have been more interesting if we had measured HIFs and the tryptophan catabolite (TRYCAT) pathway in the acute and chronic phase of the disease. Indeed, a recent meta- analysis showed that neurotoxic TRYCATs are significantly increased in acute COVID-19, while TRYCATs are known to be associated with the onset of affective, physiosomatic and cognitive symptoms (Maes, Leonard et al 2011, Kanchanatawan, Sirivichayakul et al 2018, Almulla and Maes 2022, Almulla, Supasitthumrong et al 2022). Second, although we conducted a case-control study, we also measured body temperature and SpO2 in the acute phase of illness using a retrospective cohort study design which allows to examine causal associations.…”
Section: Limitationsmentioning
confidence: 99%
“…TRYCATs with neurotoxic activities including KYN and 3-HK play a key role in IFN-α induced major depression (Bonaccorso, Marino et al 2001, Maes, Bonaccorso et al 2001). Indeed, the onset of these IFN-α-induced depressive symptoms is more strongly associated with the production of KYN (a neurotoxic TRYCAT) and an increased ratio of KYN to KA, a neuroprotective TRYCAT, than with lowered TRP levels (Bonaccorso, Marino et al 2001, Maes, Bonaccorso et al 2001, Bonaccorso, Marino et al 2002, Wichers, Koek et al 2005, Maes 2015). By inference, it was thought that also in MDD/BD, which is characterized by lowered plasma/serum tryptophan, increased neurotoxicity due to IDO stimulation could be the major culprit (Bonaccorso, Marino et al 2002).…”
Section: Introductionmentioning
confidence: 99%